Pengaruh Penyaluran Pembiayaan Koperasi Baitul Maal Wat Tamwil dengan Akad Murabahah terhadap Pendapatan Usaha Mikro Kecil Menengah di Desa Babakan Bogor (Studi Kasus: KBMT Tadbiirul Ummah) - Hasna Halimatur Rosyidah; Mukhbitah Mukhbitah; Wikiandaru Wikiandaru (ISLAMINOMICS: JOURNAL OF ISLAMIC ECONOMICS, BUSINESS AND FINANCE, 2020)
Nowadays, Indonesia is still experiencing the economic equality gap, especially in rural and urban areas. The Central Bureau of Statistics in Indonesia (2015) revealed the ratio of economic disparities between rural and urban areas by 0.41. This is clearly not in accordance with the words of Allah SWT, which reads "... so that it may not be (a benefit) going round and round among such of you as may (already) be rich.... (Al-Hashr: 7)." This ayah describes the importance of economic equality in village in order to create prosperity. The difficulty of rural communities in accessing financial facilities, in particular to develop the real sector in the form of UMKM which are the main foundation of the economy, has now helped by the existence of financial institutions KBMT. It is an alternative provider of financing facilities for UMKM in the village. One of them is KBMT Tadbirrul Ummah that has been contributing to society in the village of Babakan, Bogor. The magnitude of the KBMT Tadbirrul Ummah effect is examined using quantitative descriptive method to benchmark the dependent variable. It is the income after financing and independent variables, namely the micro loan product used. Furthermore, to get the effect of KBMT financing to UMKM, the writer conducted an analysis by comparing the advantages of KBMT respondents before and after obtaining the financing. The results showed that 62.4% of data processing development value diversity gains can be explained independent variables. The amount of BMT murabahah financing give the positive influence on changes in the business profits of UMKM with significant regression coefficient of 0.781 and on the real level of five percent. This means that if the amount of Islamic micro finance BMT increased Rp 1.000.000, the development benefits obtained by businesses will increase by Rp 781.000.